The Application of Pancasila Values ​​in the Learning Process at SDN 2 Banjar Sari, Labuan Haji District - Hazim Muhtarom; Harni Hermayana; Hulfayatullayli; Della Gousmantari; Anggun Febriyanti; Deni Priyadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study discusses the application of Pancasila values in the learning process where the application of Pancasila values is very important because Pancasila values contain noble values that can form good and noble characters. The purpose of this study is to explain more deeply regarding the application of Pancasila values in the learning process because education is very involved in introducing Pancasila values, especially in the learning process. The research method used is descriptive research with a qualitative approach. Data were collected using interviews and observations. The results of the study show the importance of the application of Pancasila Values in elementary schools, by introducing and applying Pancasila values can form good character and behavior patterns of students.